(untitled) - Karolína Červinková (Listy klinicke logopedie)
The oral intake of premature babies is made more difficult by their immaturity, so it is necessary to pay more attention to their oral intake. Globally, these babies are approached by focusing on the quality of oral intake, rather than the quantity, as a prerequisite for the formation of the mother-child bond, the optimal development of oral-motor skills, facial parts (splanchnocranium) and other related areas. For this reason, a clinical speech and language pathologist (SLP) specialising in this area features increasingly as part of the comprehensive care of premature babies with feeding problems. This often begins immediately after birth, when the newborn has difficulties with sucking, where the SLP then evaluates the quality of oral intake and, through systematic and individually designed interventions, the development of not only sucking but also of subsequent related areas is very significantly and positively influenced. This article provides some basic insight into the issues of premature babies' sucking from the point of view of a clinical speech and language pathologist, together with an overview of diagnostic and therapeutic options.